The Role of Social Work in the Construction of Smart Cities: Practices and Prospects of Digital Services - Chen, Yih-Chang; Lin, Chia-Ching (Digital Technologies Research and Applications, 2025)
The swift advancement of global digital transformation has established smart cities as a prominent trend in modern urban planning. This research examines the essential role of social work in the development of smart cities, with a particular focus on the practical application of digital service platforms, exemplified by Taiwan’s “Smart Decision‑Making Action Platform for Social Workers.” Employing a mixed‑methods approach involving 762 social workers, this study addresses four fundamental questions: (1) in what ways can social work redefine its roles within the context of smart cities, (2) what are the specific impacts of digital technology integration on social work practices, (3) what successes and challenges are associated with current digital platforms, and (4) what strategies can be employed to develop integrated social work service systems for smart cities? The findings indicate that social workers play a vital bridging role within smart city ecosystems, resulting in a 35.7% increase in service efficiency and a 47.8% enhancement in practice safety. The integration of digital technology significantly improves working conditions, reduces risks, and enhances service quality while preserving a human‑centered approach. This study introduces the Smart City Social Work Integration Model (SCSWIM) and offers evidence‑based recommendations for policy formulation and the enhancement of professional practice in digitally‑enabled urban settings.